Conocimientos sobre el embarazo precoz y actitudes preventivas en estudiantes del primer ciclo de Trabajo Social de la Universidad Nacional de Trujillo, 2021 - Alayo Vigo, Olivia Margarita (2022)
The objective of this non-experimental, explanatory and cross-sectional research was to explain the influence of knowledge about early pregnancy on the preventive attitudes of students in the first cycle of Social Work at the National University of Trujillo, 2021. The sample consisted of 23 students who met the inclusion criteria. The survey was used as a technique and through a questionnaire both the knowledge about early pregnancy and the preventive attitudes presented by the students were measured, the present research study was raised as the main objective: Explain the influence that knowledge about early pregnancy has on the preventive attitudes of students in the first cycle of Social Work at the National University of Trujillo, 2021. From the development and execution of the research work, the following types of students were evidenced: The students who have good knowledge about early pregnancy and in turn present positive preventive attitudes; Likewise, the students who have good knowledge, but have negative attitudes and, finally, the students who have poor knowledge, but have positive attitudes towards the prevention of early pregnancy. In this way, the following was concluded: From the execution of this research study, it was possible to demonstrate that knowledge about early pregnancy in the area of contraceptive methods and knowledge of the psychological consequences (low self-esteem, depression, etc. ), physical (health and nutrition problems, etc.) and social (study desertion, limited job opportunities, etc.) in the students of the I cycle of social work of the UNT, influenced the improvement of their preventive attitudes expressed in the use of contraceptive methods in their coital relations, being the most used the condom (27.6%) and in the responsible decision of postponing sexual relations (78.3%).